A Novel Oral Arginase 1/2 Inhibitor Enhances the Antitumor Effect of PD-1 Inhibition in Murine Experimental Gliomas by Altering the Immunosuppressive Environment - Pilanc, Paulina; Wojnicki, Kamil; Roura, Adria-Jaume; Cyranowski, Salwador; Ellert-Miklaszewska, Aleksandra; Ochocka, Natalia; Gielniewski, Bartłomiej; Grzybowski, Marcin M.; Błaszczyk, Roman; Stańczak, Paulina S.; Dobrzański, Paweł; Kaminska, Bozena (Frontiers in Oncology, 2021)
Glioblastomas (GBM) are the common and aggressive primary brain tumors that are incurable by conventional therapies. Immunotherapy with the immune checkpoint inhibitors is not effective in GBM patients due to the highly immunosuppressive tumor microenvironment (TME) restraining the infiltration and activation of cytotoxic T cells. Clinical and experimental studies showed the upregulation of expression of the arginase 1 and 2 (ARG1 and ARG2, respectively) in murine and human GBMs. The elevated arginase activity leads to the depletion of L-arginine, an amino-acid required for the proliferation of T lymphocytes and natural killer cells. Inhibition of ARG1/2 in the TME may unblock T cell proliferation and activate effective antitumor responses. To explore the antitumor potential of ARG1/2 inhibition, we analyzed bulk and single-cell RNA sequencing (scRNA-seq) data from human and murine gliomas. We found the upregulation of ARG1/2 expression in GBMs, both in tumor cells and in tumor infiltrating microglia and monocytes/macrophages. We employed selective arginase inhibitors to evaluate if ARG1/2 inhibition in vitro and in vivo exerts the antitumor effects A novel, selective ARG1/2 inhibitor - OAT-1746 blocked microglia-dependent invasion of U87-MG and LN18 glioma cells in a Matrigel invasion assay better than reference compounds, without affecting the cell viability. OAT-1746 effectively crossed the blood brain barrier in mice and increased arginine levels in the brains of GL261 glioma bearing mice. We evaluated its antitumor efficacy against GL261 intracranial gliomas as a monotherapy and in combination with the PD-1 inhibition. The oral treatment with OAT-1746 did not affect the immune composition of TME, it induced profound transcriptomic changes in CD11b+ cells immunosorted from tumor-bearing brains as demonstrated by RNA sequencing analyses. Treatment with OAT-1746 modified the TME resulting in reduced glioma growth and increased antitumor effects of the anti-PD-1 antibody. Our findings provide the evidence that inhibition of ARG1/2 activity in tumor cells and myeloid cells in the TME unblocks antitumor responses in myeloid cells and NK cells, and improves the efficacy of the PD-1 inhibition.